Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1039/c8fo00157j
|View full text |Cite
|
Sign up to set email alerts
|

Barley β-glucan increases fecal bile acid excretion and short chain fatty acid levels in mildly hypercholesterolemic individuals

Abstract: The cholesterol-lowering effect of barley β-glucan has been proposed to be the result of a pleiotropic effect, which involves several biological mechanisms such as gut fermentation, inhibition of intestinal cholesterol absorption and increased bile acid excretion and its synthesis. However, one of the recent studies from our laboratory indicated that increased bile acid excretion and subsequent increase in its synthesis, but not the inhibition of cholesterol absorption or synthesis might be responsible for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 21 publications
1
38
0
1
Order By: Relevance
“…As the bile acid is the converted product of cholesterol, its synthesis process in the liver has become the main pathway of cholesterol metabolism and cholesterol excretion (Chen et al ., ). It has been reported that chemical compounds such as lupin seed, paprika seed oil and β‐glucan in barley could be able to bind with bile acid in the intestine and promote the excretion of bile acid (Fontanari et al ., ; Chen et al ., ; Thandapilly et al ., ). This phenomenon consequently leads to greater amount of cholesterol converted to bile acid and results in the cholesterol‐lowering effect (Insull, ).…”
Section: Resultsmentioning
confidence: 97%
“…As the bile acid is the converted product of cholesterol, its synthesis process in the liver has become the main pathway of cholesterol metabolism and cholesterol excretion (Chen et al ., ). It has been reported that chemical compounds such as lupin seed, paprika seed oil and β‐glucan in barley could be able to bind with bile acid in the intestine and promote the excretion of bile acid (Fontanari et al ., ; Chen et al ., ; Thandapilly et al ., ). This phenomenon consequently leads to greater amount of cholesterol converted to bile acid and results in the cholesterol‐lowering effect (Insull, ).…”
Section: Resultsmentioning
confidence: 97%
“…Antihypertensive treatment is known to improve cardiac filling properties and improve diastolic function (Mattioli et al, 2004;Muller-Brunotte, Kahan, Malmqvist, Ring, & Edner, 2006;Wachtell et al, 2002). In this study, beta-glucan treatment resulted in a absorbed into blood stream directly, the gut fermentation products generated by colonic microbiota such as short chain fatty acids (SCFAs) have been shown to regulate arterial BP (Thandapilly et al, 2018). For example, previous study showed that SCFA, propionate, induces vasorelaxation in rat mesenteric arteries (Khalesi, Sun, Buys, & Jayasinghe, 2014;Pluznick, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…When they reach the colon they can be degraded by the microbiota [16]. While the largely insoluble polysaccharide cellulose is quite resistant to fermentation, the well soluble β-glucans, that are found in high amounts in oats and barley, are subject to extensive fermentation leading to the production of short-chain fatty acids (SCFAs), some of which exert beneficial effects on human health [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, β-glucans and other fibres have been shown to lower blood cholesterol concentrations, presumably by the binding of BAs and thereby decreasing their reabsorption [16,17,19]. This loss is compensated by increased synthesis of BA from cholesterol.…”
Section: Discussionmentioning
confidence: 99%